2021
DOI: 10.1097/mat.0000000000001605
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis in Extracorporeal Membrane Oxygenation (ECMO) Circuits

Abstract: Thrombosis in extracorporeal membrane oxygenation (ECMO) circuits remains a frequent complication. We characterize the location, extent, structure, and clinical implications of thrombi in 53 ECMO circuits from 46 pediatric patients. The tubing, pump, and oxygenator were examined for visible thrombi. Representative samples of thrombi were collected for histologic, immunofluorescence, and immunohistochemical analysis. Thrombi were found in 81% of ECMO circuits. The most clinically significant were inflow oxygena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…Our histological data, however, indicates that both the individual thrombus components (RBCs, fibrin, platelets, and VWF content) and the unbiased thrombus cluster-types are not associated with the respective location in the device. Similar as to our quantitative findings, a recent descriptive report, investigating 53 pediatric ECMO circuits, has shown that thrombi originating from different device locations consist of a mixture of fibrin, platelets, red blood cells, VWF, and leukocytes 19. In contrast, two descriptive reports by Hastings et al have shown that oxygenator and tubing thrombi mainly consist of RBCs and fibrin,…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Our histological data, however, indicates that both the individual thrombus components (RBCs, fibrin, platelets, and VWF content) and the unbiased thrombus cluster-types are not associated with the respective location in the device. Similar as to our quantitative findings, a recent descriptive report, investigating 53 pediatric ECMO circuits, has shown that thrombi originating from different device locations consist of a mixture of fibrin, platelets, red blood cells, VWF, and leukocytes 19. In contrast, two descriptive reports by Hastings et al have shown that oxygenator and tubing thrombi mainly consist of RBCs and fibrin,…”
supporting
confidence: 91%
“…The exact mechanisms of in‐device ECMO thrombosis remain poorly understood. Yet, only few studies investigated the composition of ECMO thrombi 14,15,19 . These reports mainly focused on the descriptive analysis of ECMO thrombi in a pediatric population, in particular RBC, fibrin, platelets, and VWF content, and will be compared with our findings throughout the discussion 14,15,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 In addition, thrombosis of the oxygenator membrane can lead to failure of the ECMO circuit, the need for frequent circuit changes, and the use of high doses of anticoagulation medications, further endangering the patient and adding a significant economic burden to the hospital/ healthcare system. 13,14 The contact of blood with extracorporeal surfaces can also lead to a robust inflammatory reaction characterized by high levels of pro-inflammatory cytokines, initiation of the complement system, stimulation of neutrophils and platelets, injury to endothelial cells and capillaries, and ultimately, worsening lung and extrapulmonary organ damage. 12,[15][16][17][18][19] This pro-inflammatory response is closely linked to an activation of the intrinsic and extrinsic coagulation pathways, creating a "thromboinflammatory" state, an effect that has been particularly prevalent in patients infected with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of blood to the extracorporeal circulation/surfaces leads to activation of the coagulation cascade, platelet dysfunction, and hemolysis, resulting in both clotting and bleeding complications for the patient 11,12 . In addition, thrombosis of the oxygenator membrane can lead to failure of the ECMO circuit, the need for frequent circuit changes, and the use of high doses of anticoagulation medications, further endangering the patient and adding a significant economic burden to the hospital/healthcare system 13,14 …”
Section: Introductionmentioning
confidence: 99%